Penerapan Naht dalam Pembelajaran Bahasa Arab: Strategi Interaktif di Madrasah Ibtidaiyah Izzul Islam - Sa’adah Fuji Astutik; Ainur Rofiq Sofa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Summarizing Arabic texts plays a crucial role in understanding and disseminating knowledge. In Arabic language learning, there is a concept known as Naht, which is the process of simplifying or condensing lengthy and complex texts into a shorter form without diminishing the core meaning contained within them. However, in reality, many students still struggle to summarize Arabic texts due to less interactive teaching methods, resulting in passive attitudes and a lack of self-confidence among students. This study aims to develop more interactive teaching techniques to enhance student participation while supporting their critical thinking skills, particularly in the ability to summarize after reading Arabic texts. This research employs a qualitative approach with descriptive methods through observation, interviews, and documentation. The results show that the application of interactive methods such as group discussions and mind mapping positively impacts students' ability to summarize Arabic texts and develop critical thinking skills. Group discussions help deepen understanding and boost students' confidence, while mind mapping facilitates the identification of core material and makes learning more engaging and easier to remember. This technique has proven effective in improving summarization skills and sharpening critical thinking, thus it is recommended for teachers to implement and further develop it in order to create an optimal learning process for students at Madrasah Ibtidaiyah Izzul Islam.